The Language of Electricity. Issue 2 (March 2020) - Kivnick, Alexandra R.; Limone, Brittanya; Jacob, Sharon E.
Abstract : ABSTRACT: Electrical devices are commonly used within the field of dermatologic surgery. With the growing role of nursing providers in the dermatologic setting, it is essential to provide education and training regarding electrical devices and concepts within the nursing community. This installment introduces electricity principles and reviews terminology associated with the electrical devices used in dermatologic procedures.